The epidemiology, demographics, and comorbidities of pulmonary and extra-pulmonary non-tuberculous mycobacterial infections at a large central Florida Academic Hospital. (December 2021) - Garcia, Cristina V.; Teo, Greg E.; Zeitler, Kristen; Jariwala, Ripal; Montero, Jose; Casanas, Beata; Aslam, Sadaf; Cannella, Anthony P.; Morano, Jamie P.
Highlights: Non-tuberculous mycoabcteria (NTM) cases have been increasing in the state of Florida, especially in the central portion of the state, where the population has been steadily increasing. Our analysis suggests that in our Mycobacterium abscessus complex was the most prevalent NTM seen in our patients, with Mycobacterium avium Complex being a distant second. Our GIS mapping of these local NTM cases describes where the patients lived relative to the organism which they grew. Furthermore, for the NTM isolates that we obtained data, we demonstrate the actual variability of antibiotic susceptibility, and with a few isolates, this was observed over time. Abstract: Rationale: In the United States, non-tuberculous mycobacterium (NTM) infections are considered an important cause of morbidity and mortality, especially in people with progressive lung disease. The state of Florida has an extremely high incidence and prevalence of NTM disease which is likely a rapidly emerging infection in the state due to environmental and demographic factors. Objectives: Adjemian et al. [1] To determine the burden of NTM disease of patients admitted to a large Central Florida academic center, Falkinham [2] to identify the most common risk factors associated with developing NTM disease in this area, and Sfeir et al. [4] to categorize antimicrobial susceptibilities and genetic resistance markers. Methods: We conducted a retrospective case review from January 1, 2011 to December 31, 2017 in a large university-associated metropolitan hospital in west-central Florida. NTM infections were identified using TheraDoc® during the study period with the inclusion criteria of any inpatient admission, culture confirmed NTM at any site, and age ≥ 12 years. Demographic variables (including residential zip code) and comorbidity data (including solid organ transplant status, HIV status and subsequent testing results, intrinsic pulmonary disease, and cancer diagnosis of any site) were collected for each patient. Microbiologic data collected included NTM species/subspecies, anatomic location of specimen collection, antimicrobial susceptibility including minimum inhibitory concentration (MIC). All collected data were analyzed within Stata/IC14.2. Geospatial relationships between zip codes, diagnosis type, and co-morbidities were computed using Arc GIS Pro. Results: Our results demonstrated that a substantial number of our inpatient cases with NTM were of the M. abscessus group, and with M. avium complex and M. fortuitum also representing the pathogen in numerous cases. Novel findings included compilation of the first hospital wide comprehensive NTM resistance plot to our knowledge. Our results did show a concordance with previous data with expected predominance of NTM inpatient cases in Caucasian males with pre-existing pulmonary disease, though additional work could be done with isolates within the transplant and immunosuppressed populations. Conclusions: Our data set demonstrates the most common species/subspecies of NTM infections and their associated conditions seen at our central Florida hospital, and includes an antimicrobial sensitivity analysis in toto. This could be insight into the possible prevalence of NTM in the area, and provides the foundation for future studies on both the acquisition and prevention for NTM infections in central Florida.